APPLICATION OF THE SNOWBALL THROWING COOPERATIVE LEARNING MODEL ON TRANSPORTATION ENGINEERING EDUCATION FKIP UNIVERSITY OF PALANGKA RAYA ACADEMIC YEAR 2017/2018 - Whendy Trissan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
This study aims to help students to more easily understand, analyze and work on the problems of each subject matter in Transportation Engineering courses and be active when learning activities in class so that it affects the learning outcomes of students. The approach and type of research used in this study is quantitative research, which is an analysis technique whose analysis is carried out using numbers and analysis using statistics. From the analysis of the data obtained the average pretest results in the experimental group amounted to 52.31 and the average value of the pretest control group obtained 53.50. While the average results of the post test in the experimental group that is equal to 83.125 and in the control class of 68. From these data it can be concluded the average value of student learning outcomes in the experimental group in which the learning process is applied to the Snowball Throwing cooperative learning model has a difference of 30.185 from the control group in the learning process carried out by the lecture method which only gained an increase of 14.5. The results of the research, analysis and discussion of research data, the following conclusions related to the research that there are differences in student learning outcomes using the Snowball Throwing cooperative learning model with the lecture method in Transportation Engineering Students of the Building Engineering Education Study Program FKIP University of Palangka Raya Academic Year 2017/2018. This difference can be seen from the learning outcomes in the experimental group that is based on the calculation results obtained an average value of 83.125. While learning outcomes in the control group by using the lecture method, which is based on the calculation results obtained an average value of 68.